Design of Expert System Diarrhea for Toddler Using K-Nearest Neighbor Algorithm (K-NN) - Silmina, Esi Putri; Hardiani, Tikaridha (Sekolah Tinggi Teknologi Adisutjipto, 2018)
Diarrhea is one of the main causes of death in children under the age of 5 years. Based on reports from the World Health Organization (WHO), 1 in 10 children died of diarrhea with 800,000 deaths per child. When toddlers suffer from diarrhea there are obstacles faced by parents when having to consult a pediatrician, for that we need a system that can store the expertise of an expert in this case a pediatrician in dealing with diarrheal diseases that occur in infants. The K-NN (K-Nearest Neighbor) algorithm was developed in this research expert system. The variables used were 14 symptoms where diarrheal diseases were classified into 6 types. The results of distance calculation show testing data (new cases) No RM 4247 approaching 3 training data (old cases) with a distance value of 2.24. The addition of the calculation of similarity in the calculation strengthens the results of the diagnosis, with the largest similarity value of 79% at No RM 1090, then the testing data (new cases) didignosis mild acute dehydration diarrhea